Safe From Harm Implementation Strategy as An Effort to Protect Children at SMPN 1 Cina Students - Listari, Ayu Widya; Rahman, Andi Abdul; Cahaya, Andi; Asdar, Muhammad; Muslimin, Muslimin (Jurnal Ad'ministrare: Jurnal Pemikirian Ilmiah dan Pendidikan Administrasi Perkantoran, 2024)
Child protection in Indonesia is an urgent problem and has many aspects and involves families, the state, society and certain child protection institutions. Therefore, it is very wise if child protection starts from the school world. Protecting children at school is important to ensure that they learn safely and comfortably. This research aims to explore strategies for implementing the Safe From Harm program at SMPN 1 Cina, to protect children from violence, neglect and exploitation. The method used was qualitative with a case study approach, involving interviews and observations from 10 informants consisting of the school, parents and student representatives. The implementation of the Safe From Harm strategy at SMPN 1 Cina has shown significant results in creating a safe, comfortable and inclusive learning environment for all students. This program has not only succeeded in reducing violence, but also built an environment that supports students' social and emotional development. With the support of all parties, SMPN 1 Cina is a clear example that collaboration in creating schools free from violence is possible and achievable. This success must be maintained and continued to ensure that every student can learn and develop in a safe and empathetic atmosphere.